PARP6 suppresses the proliferation and metastasis of hepatocellular carcinoma by degrading XRCC6 to regulate the Wnt/β-catenin pathway - Tang, Bo (Am J Cancer Res, 2020)
PARP6 belongs to the mono-ADP-ribosyltransferase family and has been shown to be involved in the genesis and development of some tumours. However, the role of PARP6 in hepatocellular carcinoma (HCC) development remains to be fully elucidated. In the current study, we demonstrated that PARP6 was expressed at a low level in HCC cells and was negatively related to the degree of tumour differentiation. Additionally, silencing PARP6 led to an increase in the proliferation, invasion and migration ability of HCC cells in both in vitro and in vivo assays. Conversely, an elevation in the PARP6 expression level had the opposite effect. Through gene chip analysis combined with experimental verification, we confirmed that PARP6 can inhibit the expression of XRCC6 by inducing degradation and thus affect the Wnt/β-Catenin signalling pathway, which contributes to the suppression of HCC. Further mechanistic investigation demonstrated that the ubiquitin ligase HDM2 can interact with PARP6 and XRCC6, and mediated the regulatory effect of PARP6 on XRCC6 degradation. Taking together, PARP6 appears to inhibit HCC progression through the XRCC6/Wnt/β-catenin signal axis and could be used as a biomarker for the clinical monitoring of HCC development.